Efektivitas Penggunaan Permainan Dahi Detektif sebagai Game Edukatif dalam Intervensi Bencana Banjir dan Kebakaran pada Anak Usia 10-11 Tahun - Tiara Marsela Triyani; Harta Prima Meza; Lovina Ausha Nessaputri; Syukriat Syukriat; Qori Gheitsa Zahira; Devi Lusiria (INDO PUBLISHING, 2026)
Indonesia has high vulnerability to floods and fires that cause psychological impacts on children. This study examined the effectiveness of the